2011
DOI: 10.1007/s00232-011-9399-x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Expression, Purification and Characterization of a Rice Voltage-Dependent, Anion-Selective Channel Isoform, OsVDAC4

Abstract: The voltage-dependent anion-selective channel (VDAC) is the most abundant protein in the mitochondrial outer membrane and forms the major conduit for metabolite transport across this membrane. VDACs from different sources show varied primary sequence but conserved functional properties. Here, we report on the characterization of a rice channel, OsVDAC4, which complements a VDAC1 deficiency in yeast. We present a consensus secondary structure prediction of an N-terminal α-helix and 19 β-strands. Bacterially exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…56 Dynamic light scattering measurements on a DynaPro-99 instrument (Protein Solutions) indicated that the average diameter of the vesicles was 460 ± 65 nm. Liposomes were subsequently incubated with moPrP aggregates for 1 h before performing the liposome swelling assay.…”
Section: Hdx-ms Measurementsmentioning
confidence: 99%
“…56 Dynamic light scattering measurements on a DynaPro-99 instrument (Protein Solutions) indicated that the average diameter of the vesicles was 460 ± 65 nm. Liposomes were subsequently incubated with moPrP aggregates for 1 h before performing the liposome swelling assay.…”
Section: Hdx-ms Measurementsmentioning
confidence: 99%
“…Four VDAC genes have been reported previously in O. sativa (Roosens et al, 2000;Al Bitar et al, 2002Godbole et al, 2011). This study has shown that there are 8 rice VDAC genes, which is the complete rice VDAC gene family.…”
Section: A B Discussionmentioning
confidence: 65%
“…At least three isoforms of VDAC are present in Nicotiana tabacum ) and five different VDACs are present in Arabidopsis thaliana, Lotus japonicus, and Medicago truncatula (Clausen et al, 2004;Wandrey et al, 2004;Lee et al, 2009). There are 4 VDACs reported in Oryza sativa (Roosens et al, 2000;Al Bitar et al, 2002Godbole et al, 2011). Interestingly, cultivated rice has more VDAC isoforms than the wild Oryza officinalis group (Ma et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…VDAC is a mitochondrial outer membrane ion channel and a critical participant in the apoptosis of animal and plant cells (Al Bitar et al, 2003;Godbole et al, 2003). In plants, over-expression of rice VDAC (OsVDAC4) induces apoptosis (Godbole et al, 2011). In animal cells, knocking down VDAC1 by small interfering RNA attenuates endostatin (ES)-induced apoptosis, while over-expression of VDAC1 enhances the sensitivity of endothelial cells to ES (Yuan S. et al, 2008).…”
Section: Os08g0199300mentioning
confidence: 99%